AGE DIFFERENCES IN THE ASSOCIATION OF NON-MEDICAL PRESCRIPTION OPIOID USE AND SERIOUS MENTAL ILLNESS. (11th November 2018) - Chan, K; Trant, J; Winston, P; Moller, M
Abstract: Overdose from prescription opioid use is the leading cause of death for all substance-related fatalities, and has been declared a public health emergency in the US. Past research on opioid misuse and mental health pathology has focused primarily on adolescents and young adults, as the age group with the highest risk. To date, there is little to no research on the relationship of opioids and mental health for older adults. This study used data from the 2016 National Survey on Drug Use and Health (NSDUH). The sample in this analysis included 37, 845 adults aged 18 and older. Weighted logistic regression analyses were used to examine the association of non-medical prescription opioid use (NMPOU) and meeting the diagnostic threshold for serious mental illness (SMI), as measured by the Kessler Psychological Distress Scale (K6). Control variables included demographics, other substance use, health and mental health. Subgroup analyses were conducted by age group. Results indicated that for those 50 and older, NMPOU is associated with increased odds of meeting the threshold for having an SMI as defined by the K6 (OR=2.30, p<.01, 95% CI: 1.26, 4.23), but not for younger age cohorts. Future research is needed to investigate the impact of opioids on mental health pathology for older adults. Public policy responding to the opioid epidemic must include allocation of resources for mental health treatment which targets older populations. There is a dire need for geriatric mental health professionals who can provide effective treatment for this at-risk population.